Teacher Readiness in Implementing the Merdeka Curriculum: A National Study of Public Schools in Mataram City - Ibrahim, Muhammad; Aisyah, Nur (Journal of Education and Social Science, 2026)
The implementation of the Merdeka Curriculum requires teachers to be adequately prepared in understanding its concepts, principles, and learner–centered instructional practices. This study aims to analyze the readiness of teachers in public schools across Mataram City to implement the Merdeka Curriculum, focusing on pedagogical competence, mastery of teaching resources, the ability to conduct authentic assessments, and the utilization of educational technology. This research employs a quantitative descriptive approach involving 120 teachers from eight public schools selected through purposive sampling. Data were collected using standardized questionnaires and brief interviews, then analyzed using descriptive statistics and simple triangulation. The findings indicate that most teachers fall into the “moderately ready” category, with an average readiness score of 72%, particularly in their understanding of the curriculum’s core concepts and adaptation of instructional methods. However, challenges remain in designing diagnostic assessments, conducting formative evaluations, and accessing intensive government-provided training. This study concludes that teacher readiness in Mataram City still requires improvement through continuous professional development, the strengthening of learning communities, and the provision of technical support in schools. These findings provide important implications for policymakers in developing systematic strategies to enhance teacher competencies and accelerate the successful implementation of the Merdeka Curriculum.